Confirmation of the importance of lymphatic leakage in the formation of axillary fluid collections after lymph node dissection for breast cancer - Mirela Mariana, Roman; Clarence, Karler; Véronique, Del Marmol; Pierre, Bourgeois (Clinical Surgical Oncology, 2025)
In patients undergoing complete axillary lymph node dissection (CALND) for breast cancer, axillary lymphatic leakages can be detected using near-infrared fluorescence imaging after subcutaneous injection of indocyanine green (ICG) into the ipsilateral hand. This study investigates the impact of these leaks on postoperative fluid volumes collected in drains (Vd) and through punctures (Vp). A total of 55 patients received a single subcutaneous ICG injection in the ipsilateral hand either the day before or on the day of surgery. Postoperative fluid volumes, including drain output (Vd) and puncture collections (Vp), were analyzed and compared in relation to the presence or absence of fluorescence detected perioperatively in axillary lymph nodes (AxLNs) and drains. Fluorescence in AxLN: The absence of fluorescence in the AxLN was associated with a tendency for lower Vd but showed no significant effect on Vp or the total volume of fluid collected (Vt ​= ​Vd ​+ ​Vp). Fluorescent Axillary Leak: Similar trends were observed for the intraoperative detection of a fluorescent axillary leak, although the statistical significance was less pronounced. Fluorescence in Drains: The absence of fluorescence in postoperative drains was significantly correlated with lower values for all analyzed parameters, including Vd, Vp, Vt, the proportion of patients requiring punctures, and the number of punctures. The findings support the hypothesis that postoperative fluid collections in the axilla after CALND are due primarily to lymphatic leakage from the arm rather than to the removal of axillary lymph nodes. The detection of fluorescence during surgery offers a foundation for targeted strategies to mitigate lymphatic leakages and associated complications. The efficacy of such approaches should be validated through a prospective, multicenter, randomized trial. •The simplest way to diagnose these leaks is through our 'touch-and-view' approach, which can also be viewed in the axilla using near-infrared imaging systems.